HEALTH SYSTEM AS A CONCEPT: CRITERIA OF MENTAL HEALTH - Rabota, Tetyana (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted considered as health system concepts and criteria highlighted mental health. The attention is focused on the impact of culture, education and media in the perception and attitude to individual mental health and health in general. The factors that form human health are noted. It is stressed that the maintaining health and normal life of citizens are the most important goals of the international community, these reflected in the principles of European policy Health-2020: Fundamentals of European Policy in Support of Actions of the State and Society in the Interests of Health and Well-Being». It is shown the factors that form the human health. The three levels are defined that describes the value of «health». Much attention in the article is given to the importance of understanding of individual perception of the concept «mental health». The article gives information on further perspective of research, which is determining in the actual individual categorization of the concept «mental health».